Evaluasi Pelaksanaan Pembelajaran Online (E-Learning) Selama Masa Pandemi COVID-19 di SDI Sabilillah Sidoarjo - Izzudin, Muh Ariz; Baalwi, Muhammad Assegaf; Ali Thoufan, Moch. Fabet (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
This study aims to evaluate the implementation of online learning (e-learning) during the Covid-19 pandemic at SDI Sabilillah. This type of research is evaluation research with a quantitative research approach. The method used in this research is descriptive method. Data collection techniques in this study used teacher and student questionnaires based on the CIPP evaluation model (context, input, process, product). The sample in this study was 11 teachers and 15 high class students. The results of this study indicate that the score obtained by the teacher based on the understanding and management of e-learning based learning is in the high category with a percentage of 87.78%. The scores obtained by students based on understanding of e-learning based learning were included in the high category with a percentage of 82.16%. Based on the discussion obtained from the results of the questionnaire, e-learning-based learning activities were carried out well (structured, on schedule and coordinated). Applications that are widely used are google classroom and google meet. Meanwhile, the obstacles experienced by teachers and students were the unstable internet network and difficulties in understanding the explanation from the teacher.